Prevalence and Resistance Profile of Acinetobacter baumannii Isolated from Clinical Specimens at a Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Acinetobacter baumannii is one of the significant pathogens to cause healthcare-associated infections worldwide. It is difficult to control and the infections caused by it are difficult to treat, because it is multidrug resistant.Objective: This study was conducted to determine the prevalence and antimicrobial resistance pattern of Acinetobacter baumannii at Dhaka Medical College Hospital, Dhaka, Bangladesh over a 12 months period.Methodology: This retrospective study was carried out over a period of one year from July 2014 to June 2015 in the department of Microbiology at Dhaka Medical College Hospital, Dhaka, Bangladesh. Antimicrobial susceptibility testing of the isolates was performed by the disk diffusion method as recommended by Clinical Laboratory and Standards Institute CLSI.Results: Non duplicate 28 A. baumannii were isolated out of a total 191 pathogenic Gram negative isolates (14.66% prevalence). The most frequently isolated A. baumannii was from ICU patients (75%) followed by inpatients (18%) and outpatients (7%). Most of the isolates were recovered from tracheal aspirates (75%). The resistance rates were higher than most of the internationally reported levels. Cephalosporins, aminoglycosides, fluoroquinolones and even carbapenems are becoming practically ineffective, where the colistin elicited the highest susceptibility levels.Conclusion: This study has guided the empirical therapy and suggest that surveillance of antimicrobial resistance of Acinetobacter baumannii is necessary.Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 177-180